Population growth of Moina sp. fed with different diets for use in larviculture and aquarium farming (Research, Society and Development, 2021)
The aim of the research was to evaluate the population growth of Moina sp. fed four diets for a period of 14 days. The initial density was one adult mill/L-1 of water. The mills were cultivated in 20 transparent plastic containers with a useful volume of 20L-1. The water temperature, pH, dissolved oxygen and electrical conductivity were checked daily. Four types of diets were tested and five samples of one liter were collected daily from each culture tank, where they were filtered through an 800µ sieve and the organisms placed in a 50mL container with the help of a pipette, for total counting under a stereomicroscope with magnification of up to 25x. The population parameters evaluated were: maximum density of organisms; day of maximum density; specific growth rate; doubling time and yield. The results were submitted to the F test for analysis of variance and linear regression analysis with the aid of the SAS® statistical package. The physical-chemical parameters of temperature, pH, dissolved oxygen and electrical conductivity remained within the recommended range for cultivation. However, for the population parameters of maximum density (diet 4) and population growth rate (diet 3), they presented statistical difference in relation to the other evaluated diets. The parameter Doubling time (Td) showed no significant difference between the evaluated diets. The most suitable diet for the cultivation of Moina sp. was treatment 4 which contained in its composition Microalgae Scenedesmus subspicatus, fermented fish feed, Aptamil premium and Yeast (Saccharomyces cerevisiae).